Comparative analysis of the impact of modern cavity disinfectants on dentin bond strength - Gümüş Ayaz, Simge; Sonkaya, Ezgi; Keçeci, Gökçe (Frontiers in Materials, 2025)
The durability of the hybrid layer, which forms the basis of successful bonding in restorative dentistry, depends on the stability of collagen fibrils. Dentin matrix metalloproteinases degrade the collagen structure over time, leading to a reduction in bond strength. Therefore, MMP inhibitors play a crucial role in maintaining bond durability. The study aims to evaluate and compare the short-term (24 h) and long-term (12 months) effects of dentin pretreatment agents -chlorhexidine (CHX), quercetin (QC), naringin (NR), riboflavin (RF), and α-tocopherol (α-TF)- on bond strength. A total of 144 extracted human molars were collected and randomly divided into six groups: control (no treatment), 2% chlorhexidine, 1% QC, 1% Nar, 3% riboflavin, and 10% α-TF. The solutions were prepared and applied to the dentin surfaces for 60 s, followed by the application of All-Bond Universal adhesive and composite resin. Following the bonding procedure, a nanohybrid flowable composite was applied onto the dentin surface of each tooth using a starch tube, forming a cylindrical specimen with a bonding area of 1 mm2 (1 mm in diameter and 1 mm in height). Half of the specimens in each group (n = 12) were tested for micro shear bond strength (μSBS) after 24 h of storage, while the remaining specimens underwent thermocycling to simulate 12 months of aging before μSBS testing. To determine the μSBS, each bonded specimen was subjected to a μSBS test in a universal testing machine (MOD Dental MIC-101, Esetron Smart Robotechnologies, Ankara, Turkey) equipped with a 5-kN load cell and featuring a lower fixed and an upper movable compartment, operating at a crosshead speed of 0.5 mm/min. After μSBS testing, failure modes were determined using a stereomicroscope. Data were analyzed using one-way analysis of variance (ANOVA) followed by Tukey’s post hoc tests with p ˂ 0.05 as the significance level. Results of the one-way ANOVA test revealed that, at the end of 24 h, the highest μSBS was observed in the QC group, followed by CHX and NG, all of which showed significantly higher bond strength than the α-TF group (p < 0.05). After 12 months of aging, an increase in SBS was observed in the QC, RF, and naringin groups, whereas a decrease was noted in the Con, CHX, and α-TF groups. QC and NG are natural and effective agents that can be alternatives to CHX in dentin pretreatment. QC showed promise in terms of long-term success, especially after thermal aging, showing the highest bond strength.